Antibacterial, hemoglobin/albumin-interaction, and molecular docking properties of phytogenic AgNPs functionalized by three antibiotics of penicillin, amoxicillin, and tetracycline. (March 2022) - Alavi, Mehran; Karimi, Nasser
Abstract: Phyto-derived silver nanoparticles (AgNPs) were modified by three antibiotics including penicillin, amoxicillin, and tetracycline to measure antibacterial activity against Gram-positive and Gram-negative bacteria. According to disc diffusion assay, Staphylococcus aureus exhibited a higher sensitivity compared to Escherichia coli and Pseudomonas aeruginosa under AgNPs/tetracycline stress. Damage of the cell envelops of S. aureus and E. coli as sensitive bacteria under MIC concentrations of Ag NPs/tetracycline was observed by SEM images. AFM technique showed a smaller size of albumin protein (8–13 nm) with a higher level of roughness equals to 74.87 nm relative to hemoglubin (5–6.9 nm) by roughness value of 47.04 nm. Interaction of main secondary metabolites includes nootkatone, nootkatin, daphnauranol C, α-Cyperone, (E)-Nerolidol, and (Z)-α-Bisabolene epoxide surrounding phyto-derived AgNPs with the binding cavities of exfoliative toxin A and exfoliative toxin B as virulence factors of S. aureus was evaluated by molecular docking study. Among these natural compounds, daphnauranol C had the suitable binding affinity as value of ˗ 6.4 kcal/mol compared with other metabolites. Based on the results of this study, tetracycline and daphanuranol C can be considered to further evaluations to obtain novel formulation of AgNPs as an efficient weapon against bacterial infections. Highlights: Tetracycline antibiotic can synergize antibacterial activity of phytosynthesized AgNPs against E. coli, S. aureus, and P. aeruginosa. Conjugation of antibiotics with bio-derived AgNPs is resulted from interaction of amino and hydroxyl functional groups of antibiotics with natural compounds around NPs. Antibiotics attached to the surface of NPs in the sites between the herbal materials. The stable and suitable binding affinity was observed for daphnauranol C and nootkatin toward exfoliative toxin A and B, respectively.